MODIFIKASI DAN INOVASI OLAHAN KELAPA MUDA MENJADI PUDING DOGAN SEBAGAI PROGRAM MBKM MAHASISWA INDO GLOBAL MANDIRI - Aling Palinggau; Lesi Hertati; Asmawati Asharie (Transpublika Publisher, 2022)
Natural resources are resources obtained from nature and can be utilized to meet the needs of human life. Abundant natural resources if not managed properly will be in vain, because this requires a community that is entrepreneurial, creative and innovative in taking advantage of these opportunities. Therefore, I am a UIGM student who wants to make the latest changes and innovations around Km 14 Palembang, namely